Hubungan Tingkat Pendidikan dengan Perilaku Kader Jumantik dalam Melaksanakan Pemberantasan Sarang Nyamuk (PSN) DBD 3M Plus di Desa Mojorejo Kecamatan Jetis Mojokerto - HIDAYATI, RINA NUR; KUSMANINGRUM, AJENG (MEDICA MAJAPAHIT, 2015)
Dengue fever is often called Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection. Dengue transmission occurs through the bite of the female Aedes aegypti mosquito which carries the dengue virus have from other people. This researchpurpose to determine the relationship of education level to the behavior kader jumantik in carrying mosquito nest eradication (PSN) 3M Plus DBD in the Village District of Jetis Mojorejo Mojokerto. In thisresearch using analytic design with cross sectional method. The population in this research is in the village kader jumantik Mojorejo Mojokerto District of Jetis is 26 people. Sampling in this research using saturation sampling technique using all the sampled population is 26 people. The results showed that most respondents have secondary education (high school) has a good behavior is 80% and 20% have unfavorable behavior.But nearly half those obtained basic education (elementary and junior high school) has a good behavior that is 47.6% so there are other factors that influence the behavior of the environment in addition to education and willingness example.Analysis of the data used is CrossTab (Cross Tabulation). For further research is expected in the data retrieval is not only using the questionnaire as a measure of behavior but can make observations (observation) directly to the kader jumantik to assess behavior.Keywords: Dengue Hemorrhagic Fever (DHF), Kader Jumantik, Education, Behavior